Islam, blasphemy, and human rights in Indonesia : the trial of Ahok - Peterson, Daniel (Daniel P.) (Oxob : Routledge, 2020)
'Using the high-profile 2017 blasphemy trial of the former governor of Jakarta, Basuki'Ahok' Tjahaja Purnama, as its sole case study, this book assesses whether Indonesia's liberal democratic human rights legal regime can withstand the rise of growing Islamist majoritarian sentiment. This book analyses whether a 2010 decision of Indonesia's Constitutional Court has rendered the liberal democratic human rights guarantees contained in Indonesia's 1945 Constitution ineffective. Key legal documents, including the indictment issued by the North Jakarta Attorney-General and General Prosecutor, the defence's'Notice of Defence', and the North Jakarta State Court's convicting judgment are examined. The book shows how Islamist majoritarians in Indonesia have hijacked human rights discourse by attributing new, inaccurate meanings to key liberal democratic concepts. This has provided them with a human rights law-based justification for the prioritisation of the religious sensibilities and religious orthodoxy of Indonesia's Muslim majority over the fundamental rights of the country's religious minorities. While Ahok's conviction evidences this, and the book cautions that matters pertaining to public religion will remain a site of contestation in contemporary Indonesia for the foreseeable future'--
Ahok and blasphemy : an introduction -- Liberal democracy and human rights in Indonesia -- Human rights discourse coalitions in contemporary Indonesia -- From pramuka to trial -- A legal defense to blasphemy -- The verdict -- Legal literacy, fatwas and the Majelis Ulama Indonesia -- Ahok and blasphemy : findings.
Bibliography : page [207]-218.
Buku bacaan asas siswazah Fakulti Pengajian Islam.
Keywords: Purnama, Basuki Tjahaja -- Trials, litigation, etc; Blasphemy -- Law and legislation -- Indonesia; Blasphemy -- Indonesia; Trials (Blasphemy) -- Indonesia; Blasphemy (Islam); Islam and politics -- Indonesia; Human rights -- Indonesia; Human rights -- Religious aspects -- Islam